Amkhoi Geopark: Geotourism and Socio-economic Development of the Rural Areas of Chaupahari Forest and Adjoining Area, Birbhum, West Bengal, India - Saha, Bikas (The Nucleus, 2023)
Tourism that encourages or intensify the distinctive geological character of a place is called as geotourism. Interpretation, promotion and preservation of geological characters are the main focuses of the geotourism. Different abiotic ingredients, biotic components and cultures are involved in geotourism and as a result, this tourism redecorates its busyness. Geotourism represents the upgradation and shielding of the geoheritage sites by education and interpretation. This new form of tourism is environmentally futuristic. By popularizing tourist places into geosites, geotourism protects the geopark with the understanding of geologists. India is rich in georesources and geosites. It shows variety and uniqueness in terms of geological characteristics, types of rocks, fossils and landscapes but little attention has been given while acknowledging the geoparks and geoheritage sites. Geological sites with tourism potential and recreational potential will play important roles in socio-economic development. Angiosperm wood fossils have been discovered in the year 2006 from a tribal village, named Amkhoi, near Chaupahari forest, Illambazar of Birbhum district. After the inauguration of a fossil park here in Amkhoi in the year 2018, its success encourages its extension and further planning for geotourism. The Wood Fossil Park at Amkhoi attempts to integrate economic benefits for the local community by imparting education and awareness on the geo-site and hence is a good stride for attaining sustainability perspectives.